The Carr Fire Vortex: A Case of Pyrotornadogenesis? - N. P. Lareau; N. J. Nauslar; J. T. Abatzoglou (Geophysical Research Letters)
Abstract Radar and satellite observations document the evolution of a destructive fire‐generated vortex during the Carr fire on 26 July 2018 near Redding, California. The National Weather Service estimated that surface wind speeds in the vortex were in excess of 64 m/s, equivalent to an EF‐3 tornado. Radar data show that the vortex formed within an antecedent region of cyclonic wind shear along the fire perimeter and immediately following rapid vertical development of the convective plume, which grew from 6 to 12 km aloft in just 15 min. The rapid plume development was linked to the release of moist instability in a pyrocumulonimbus (pyroCb). As the cloud grew, the vortex intensified and ascended, eventually reaching an altitude of 5,200 m. The role of the pyroCb in concentrating near‐surface vorticity distinguishes this event from other fire‐generated vortices and suggests dynamical similarities to nonmesocyclonic tornadoes.